Intimate lies and the law - Hasday, Jill Elaine (New York, NY : Oxford University Press, 2019)
Suppose you discovered one day that the foundations of your life were shakier than you ever imagined. An intimate relationship that you thought was grounded in trust actually depended on deception. After the initial shock and sadness, you might wonder whether the law will help you secure redress for your injuries. But most deceived intimates get no help from the courts, even when they have endured significant financial, physical, or emotional harm. Why not? Deception within intimate relationships can cause severe-even life-altering-damage. But the law has shielded this persistent and pervasive source of injury, routinely denying deceived intimates access to the remedies that are available for deceit in other contexts. This text systematically examines deception in sexual, marital, and familial relationships and uncovers the hidden body of law that governs such deceit.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 11, 2019).
Keywords: Fraud -- Social aspects -- United States; Domestic relations -- United States; Law; Laws of specific jurisdictions & specific areas of law